Notes on Elaphoglossum (Lomariopsidaceae) section Polytrichia subsection Hybrida in Mexico and Central America - Rojas-Alvarado, Alexander Fco (2003)
In Elaphoglossum sect. Polytrichia subsect. Hybrida six new species are described: E. angustioblongum A. Rojas, E. baquianorum A. Rojas, E. cotoi A. Rojas, E. jinoteganum A. Rojas, E. neeanum A. Rojas and E. silencioanum A. Rojas. New combination is made for Elaphoglossum mexicanum (E. Fourn.) A. Rojas. Two species are reported: E. barbatum (H. Karst.) Hieron. and E. scolopendrifolium (Raddi) J. Sm. Two species are redefined: E. erinaceum (Fée) T. Moore and E. tambillense (Hook.) T. Moore. E. pallidum (Baker ex Jenman) C. Chr. is eliminated for Mexico and Central America. Of the new species only E. neeanum is present outside of the region. A key is given to those species in Mexico and Central America